PENGARUH PENGELOLAAN MODAL KERJA DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA INDUSTRI PULP & PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 – 2014 - Alwiyah "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to analyze and determine the effect of working capital management and capital structure on profitability. Where the independent variable in this study is the management of working capital (turnover of working capital) and capital structure (debt to equity rati) the dependent variable is an indicator of profitability with a return on investment (ROI).The sample used is secondary data derived from the financial statements of pulp & paper listed in the Indonesia Stock Exchange (BEI) in 2010-2014. Samples taken by purposive sampling and sample that met the selection criteria. The samples used were as much as 6 industry. Analysis of data using multiple linear regression analysis with statistical test of hypothesis testing and statistical tests f t-assisted software SPSS 21.These results indicate that management of working capital and capital structure simultaneously no significant effect on profitability. And partially working capital management and capital structure also has no significant effect on profitability. This indicates that the variable X does not affect the Y either simultaneously or Parsian.Keywords: Management of working capital, capital structure and profitability